Los padres en la psicoterapia de los niños - Gómez Arango , Ana Cristina (2022)
This article discusses the place of parents in the psychotherapy of their children. It summarizes the five possibilities the therapist has to approach the relationship with the parents of the child for whom the appointment is requested: exclude them from treatment, keep them informed, let them take part in the sessions with their child, treat them simultaneously but separately , and finally work directly with the parents without the child being present. It concludes that the relationship with the parents is fundamental and indispensable, and proposes that the extent and manner in which the work with the parents is done is not a dogmatic and unilateral decision, but the result of an evaluation of the specific conditions of the case. The article of fers a number of detailed therapeutic recommendations on the treatment of children and the role of the parents in their work